Understanding the role of Polycomb-like proteins in cellular quiescence and cancer - McCole, Rachel (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
Polycomb proteins are a class of chromatin modifying complexes that are essential regulators of development, differentiation and maintenance of cell lineage. Polycomb proteins exist in two large, distinct, multimeric complexes, Polycomb repressive complex 1 and 2 (PRC1 & PRC2). PRC2 is responsible for all mono-, di- and trimethylation of lysine 27 of histone H3 (H3K27) and is composed of the core containing, EZH1 or EZH2, together with SUZ12, EED and RBBP4/7. Several studies have also characterised several accessory proteins, JARID2, AEBP2, PALI1, EPOP, PHF1/MTF2/PHF19 (alternatively referred to as PCL1/2/3) and recently EZHIP which interact with the core complex to regulate PRC2 activity and function in the recruitment of the complex to chromatin. EZH2 and the Polycomb-like proteins, MTF2 and PHF19, are regulated by E2F transcription factors and are highly expressed in rapidly growing cells, whereas PHF1 is reported to be a p53 target and found to be primarily expressed in slower growing or quiescent cells. Quiescence (also referred to as G0) is a reversible cellular state during which cells are not proliferating but ready to re-enter the cell cycle upon external stimulus. In this PhD thesis, I have characterised the role of Polycomb-like proteins in cellular quiescence and cancer. Firstly, I have analysed the assembly of a PHF1-p53 complex and the genome-wide localisation of p53 in quiescent human fibroblasts. I have also identified a distinct form of PRC2, called G0-PRC2, which predominates in quiescent or non-proliferating cells and is refractory to PRC2 inhibition or degradation. Finally, using a PRC2-focused CRISPR-Cas9 screen, I have identified regions within PHF1 of functional dependency. Taken together, I believe that these results will contribute to a better understanding of Polycomb proteins during cellular quiescence and raise the intriguing question of quiescent cells being insensitive to PRC2 inhibition or degradation suggesting a cautionary note in the treatment of cancers with PRC2-targeting drugs.
Keywords: PHF1; polycomb; quiescence